(untitled) (International Journal of Ayurveda and Pharma Research, 2019)
Bhasma occupy the highest attention and have got a very unique place because of their small doses, tastelessness, quick action, easy absorption and also their prolonged shelf life, wide range of therapeutic efficacy and better rejuvenating (Rasayana) effects. Metals and minerals are integral part of therapeutics in Ayurveda and Tamra is one of such metals which if properly processed and detoxified is useful in many diseases. But if not processed properly it shows many ill effects called Ashtmaha Dosha. In the present study Tamra Bhasma was prepared by using Tamra Patra. This study included procedures like Shodhana, Marana, Amrutikarana as per classical texts. 380gm of raw Tamra Patra were taken. Samanya and Vishesha Shodhana were done as per reference of Rasa Ratna Samuchya. After complete Shodhana, total 350gm Shudha Tamra was obtained. Loss in weight after Shodhana may be due to loss in impurities present in raw Tamra. Total 21 Puta were given in the electrical muffle furnace to prepare Tamra Bhasma. Specific temperature pattern was adopted for Puta in the electrical muffle furnace. Total 300gm of Tamra Bhasma was obtained. After each Puta there was significant loss in weight of Tamra may be due to loss in hardness and impurities. Marana was followed by Amrutikarana and net weight of Tamra Bhasma obtained was 330gm. 30gm weight gain may be due to the organic material used for the Amrutikarana process. Color of Bhasma became black after Amrutikarana.